Algicidal characteristics of novel algicidal compounds, cyclic lipopeptide surfactins from Bacillus tequilensis strain D8, in eliminating Heterosigma akashiwo blooms - Shao, Xueping; Xie, Wanxin; Liang, Yiling; Luo, Guiying; Li, Ling; Zheng, Wei; Xu, Qingyan; Xu, Hong (Frontiers in Microbiology, 2022)
Heterosigma akashiwo blooms have caused severe damage to marine ecosystems, the aquaculture industry and human health worldwide. In this study, Bacillus tequilensis D8 isolated from an H. akashiwo bloom area was found to exert high algicidal activity via extracellular metabolite production. This activity remained stable after exposure to different temperatures and light intensities. Scanning electron microscopy observation and fluorescein diacetate staining indicated that the algicidal substances rapidly destroyed algal plasma membranes and decreased esterase activity. Significant decreases in the maximum photochemical quantum yield and relative electron transfer rate were observed, which indicated photosynthetic membrane destruction. Subsequently, the algicidal compounds were separated and purified by high-performance liquid chromatography and identified as three surfactin homologues by interpreting high-resolution electrospray ionization mass spectrometry and nuclear magnetic resonance spectroscopy data. Among these, surfactin-C13 and surfactin-C14 exhibited strong algicidal activity against three HAB-causing species, namely, H. akashiwo, Skeletonema costatum and Prorocentrum donghaiense, with 24 h-LC50 values of 1.2-5.31 μg/mL. Surfactin-C15 showed strong algicidal activity against S. costatum and weak algicidal activity against H. akashiwo but little activity against P. donghaiense. The present study illuminates the algicidal characteristics and mechanisms of action of surfactins on H. akashiwo and their potential applicability in controlling harmful algal blooms.